PENGARUH DISIPLIN KERJA, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT CIPUTRA SENTRA - Dinyati, Ririen Eka; Pawirosumarto, Suharno (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
This study is determine the effect of work discipline, organizational culture and job satisfaction on employee performance of PT Ciputra Sentra. The type of research used is quantitative research type with survey method where the research instrument is a questionnaire. Population of all employees of PT Ciputra Sentra and with the sample of 98 people. The method of analysis used is multiple linear regression. Research result show that: (1) work discipline has a positive and significant effect on employee performance; (2) organizational culture has a positive and significant effect on employee performance; (3) job satisfaction has a negative and does not significant effect on employee performance; (4) simultaneously work discipline, organizational culture and job satisfaction have a positive and significant effect on employee performance.